Securities operations : a guide to trade and position management - Simmons, Michael (J. Wiley, 2002)
The operational activities that follow a trade are an important and essential part of the securities industry's business. Written by an author with many years experience within this sector, Securities Operations: A Guide to Trade Position Management sets out to demystify the subject and provides a thorough, step-by-step introduction to securities operations.